Peran Karang Taruna Kemiling Dalam Meningkatkan Partisipasi Pemuda di Bidang Sosial dan Politik - Desta Prianti; Adinda Salsabila Rizky Oktavia; Sujatnico Sujatnico; Ana Mentari; Rima Yuni Saputri (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This research aims to examine the role of Karang Taruna Kemiling in increasing youth participation in the social and political fields. Using a descriptive qualitative approach, data is collected through interviews, observations, and documentation. The results of the study show that Karang Taruna Kemiling has succeeded in empowering youth through various youth programs, such as social activities, skills training, and political education programs. Youth not only develop personally through arts, sports, and social activities, but also become increasingly aware of their role in the life of society and the state. Political education applied through participatory methods has increased the critical awareness, leadership, and social responsibility of youth. Karang Taruna Kemiling is an example of how youth organizations are able to become a moral force, social control, and agent of change in society.